Efecto del color del enfundado y aplicación de fitorreguladores sobre el desarrollo y calidad del plátano CV. barraganete (Musa aab simmonds) - Basurto Peñarrieta, Karen Katherine (2019)
The sheathe (protection of the cluster) and application of phytoregulators directed towards the cluster, is a practice that is used to improve the quality of the cluster. This research was carried out in Las Habras site corresponding to Canuto parish, canton Chone, it was carried out from March 2018 to March 2019, with the objective of evaluating the effect of the color of the sheathing and application of phytoregulators on the development and quality of the banana cv . Barraganete. The plant material used was the banana cv. Dwarf Barraganete from a plantation of eleven months of age. A completely randomized design (DCA) was used in factorial arrangement A x B + 2 with 20 treatments and three repetitions, with a total of 60 experimental units. The experimental unit was made up of three banana plants cv. Barraganete, which were selected in the field in the pre-flowering phase. The sheathing (cluster protection) and the application of phytoregulators in the results obtained in the field didn’t significantly influence the yield and quality of the dwarf barraganete plantain, which if carried out could increase the production costs unnecessarily. As soon as the results obtained in the laboratory showed significant effects in the cold room on the green time of the fruit and for firmness of it, in terms of Brix degrees they didn’t significantly influence the colors of covers in any of the environments on the hanger, which evidences this variable is independent of these factors. For the green life of the fruit in two environments (normal-cold) of hanger and the firmness of the fruit, it was significantly influenced by the phytoregulators N-large and X-cyte, while the combination of both products didn’t significantly influence these variables. The variable degrees brix wasn`t significantly influenced by any of the phytoregulators evaluated, which indicates that this variable doesn`t depend on the application of phytoregulators.